2007
DOI: 10.1111/j.1399-0039.2007.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐G polymorphism in a Polish population and reproductive failure

Abstract: To investigate whether human leukocyte antigen (HLA)-G gene polymorphism is associated with reproductive failure in a Polish population, we sequenced exons 2-4 of the HLA-G gene in 58 couples with three recurrent spontaneous abortions (RSAs) in the first trimester of pregnancy and 58 fertile control couples. We identified 12 different HLA-G alleles. Neither allele was found to be associated with an increased risk of RSA in the population. HLA-G allele sharing was similar in couples with RSA and in control fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 39 publications
(42 reference statements)
5
25
1
1
Order By: Relevance
“…Some studies did not find any association between HLA-G and recurrent spontaneous abortion [65,[85][86][87][88][89] or preeclampsia [90][91][92]. However, significant associations between HLA-G*01:05N, HLA-G*01:01:03 and HLA-G*01:04 alleles and recurrent spontaneous abortion have been documented in Caucasian populations [79,93], and in French and Chinese populations, the HLA-G*01:06 allele has been associated with preeclampsia [94,95].…”
Section: Hla-g and Pregnancy Disorders (Recurrent Pregnancy Loss Prementioning
confidence: 97%
See 1 more Smart Citation
“…Some studies did not find any association between HLA-G and recurrent spontaneous abortion [65,[85][86][87][88][89] or preeclampsia [90][91][92]. However, significant associations between HLA-G*01:05N, HLA-G*01:01:03 and HLA-G*01:04 alleles and recurrent spontaneous abortion have been documented in Caucasian populations [79,93], and in French and Chinese populations, the HLA-G*01:06 allele has been associated with preeclampsia [94,95].…”
Section: Hla-g and Pregnancy Disorders (Recurrent Pregnancy Loss Prementioning
confidence: 97%
“…Xue et al, [100] recurrent spontaneous abortion sequencing nosignificantdifferencebetweenrecurrentspontaneous abortion and any HLA-G allele in a Polish population Sipak-Szmigiel et al, [86] recurrent spontaneous abortion PCR significantelevatedfrequenciesofthegenotypeswith14bp polymorphism and the SNP3127 (C/G) in the 3' UTR in RSA women of Caucasian origin…”
Section: Diseasementioning
confidence: 99%
“…Among these, 4 studies were excluded due to duplicate publications [32][33][34][35], three had incomplete data on allele and genotype frequency which we failed to get by emails to the corresponding authors [36][37][38], and an additional one was excluded due to the absence of a control group [39]. Consequently, the remaining 17 case-control studies which examined the association between the HLA-G 14-bp polymorphism and RM were finally included [12,17,[25][26][27][40][41][42][43][44][45][46][47][48][49][50][51] (Fig. 1).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…Association between RM and HLA-G 14-bp insertion/deletion polymorphism allele Sixteen studies were included in assessing the association between HLA-G 14-bp insertion/deletion polymorphism allele and RM [12,17,[25][26][27][40][41][42][43][44][45][46][47][48][49][50]. As shown in Fig.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…Interestingly, a 100% presence of HLA-G*010401 was seen in the 11 abortion cases, while it was present in only 51.9% of the cases that were a success. [77] In 2006, a Chinese team could not find the association between HLA-G and RSA; [78,79] also, a Polish study failed to do so, [80] albeit the team suggested that nonsignificance was probably due to the small sample size. [81] Two other negative studies were published -one in 2010 that analyzed 143 RSA and 150 control couples in the Indian population [82] and another one in 2012 on an Iraqi population of 50 RSA and 50 control women.…”
Section: "Wrong" Hla Programmingmentioning
confidence: 99%